2014
DOI: 10.1007/s00701-014-2310-7
|View full text |Cite
|
Sign up to set email alerts
|

What happens to the bone flap? Long-term outcome after reimplantation of cryoconserved bone flaps in a consecutive series of 92 patients

Abstract: BACKGROUND: Reimplantation of cryoconserved autologous bone flaps is a standard procedure after decompressive craniotomies. Aseptic necrosis and resorption are the most frequent complications of this procedure. At present there is no consensus regarding the definition of the relevant extent and indication for surgical revision. The objective of this retrospective analysis was to identify the incidence of bone flap resorption and the optimal duration of follow-up. METHODS: Between February 2009 and March 2012, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…11,13,24 This trial has also confirmed that the cranioplasty procedure is not without significant complications, although the very low rate of primary infections requires further consideration.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…11,13,24 This trial has also confirmed that the cranioplasty procedure is not without significant complications, although the very low rate of primary infections requires further consideration.…”
Section: Discussionmentioning
confidence: 69%
“…16 There will always be some degree of subjectivity when making these types of assessments, although for those bone flaps that were deemed to be a complete failure, there was little doubt that cranial protection was compromised. However, as noted by Stieglitz et al, 24 a number of patients with significant resorption did not spontaneously report this occurrence and were unaware that there was a potential problem. This highlights the need for longterm clinical and radiological surveillance, especially in young adults.…”
Section: Bone Flap Resorptionmentioning
confidence: 92%
“…11,12 The procedure itself is technically straightforward, however it is becoming increasingly apparent that it is associated with relatively high morbidity and a significant failure rate due to either infection or autologous bone flap resorption. [13][14][15][16][17][18][19][20] When this 'failure' occurs further surgery is required in order to remove the primary cranioplasty and either commence antibiotics with a view to performing a delayed secondary reconstruction or replace the resorbed autologous bone with a secondary titanium cranioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the fragmented bone flaps or those implanted in patients undergone Ventriculo-peritoneal shunts showed a higher incidence of bone resorption causing bone flap collapse. 11 In a retrospective analysis by LH Stieglitz et al 15 100 patients were reimplanted with a cryopreserved autologous bone flap. Out of…”
Section: Review Of Evidencementioning
confidence: 99%
“…17 The incidence of complication is linked to patients age in many cases and is more frequent in children than adults. 15 Intracorporeal preservation is a way of preserving cranial bone flaps. The flaps are stored in subcutaneous pouches in the abdominal wall.…”
mentioning
confidence: 99%